Analysis of Farmers’ Indigenous Knowledge, Perceptions, and Practices Used in the Control of Parasitic Weed Striga among Maize and Sorghum Farmers in Northern Nigeria - Suleiman, Muhammad Sabiu; Abdulrahaman, Lado; Hussaini, Muhammad Auwalu; Bello, Tasi'u Tukur; Isa, Halima Mohammed; Ibrahim, Hassan; Dawaki, Mansur U; Fagge, Aminu Alhassan; Aliyu, Kamaludden Tijjani; Kamara, Alpha Y (Department of Agronomy and Horticulture, IPB University, 2025)
This study examined the socio-economic impact of the parasitic weed Striga infestation and the effectiveness of local and conventional control measures in Nigeria’s Gombe, Kano, and Jigawa States. Cross-sectional data from 925 respondents in 2020 was analyzed using descriptive and inferential statistics. Most respondents were male (94.8%), married (85%), and engaged in crop production (64%). The average landholding per household was 2 hectares, primarily used for cereal and legume cultivation, such as maize, sorghum, cowpea, and millet. The majority practiced mixed cropping (88%). Soil texture, moisture retention, color, and grass species appearance were used to assess farmland fertility. Striga infestation’s negative effects included stunted growth (59%), yellowing of crops (57%), yield decline (51%), and soil fertility reduction (19%). Respondents considered continuous cropping (63%), low fertilization (89%), poor crop management (79%), low rainfall (45%), and high temperature (45%) as the main causes of Striga infestation. Farmers used various methods for control, including appropriate fertilizer application (75%) and weeding (68%). Indigenous methods like a mixture of salt and potash and Parkia fruit powder were also common. The effectiveness of indigenous and conventional methods showed no significant difference between Jigawa and Katsina. In conclusion, Striga infestation significantly threatens crop production, income, and food security. It can be managed through both conventional and indigenous methods. Efforts should focus on educating farmers about agronomic practices to mitigate Striga infestation and promote the adoption of Striga-resistant crop varieties, especially in Striga-prone areas.